PERANCANGAN WEB PAGES INFORMASI PROGRAM BERITA DAN ACARA TVRI STASIUN ACEH - Saputra, Hendra (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2021)
The purpose of this research is to identify and design an information system for news and program programs at TVRI Aceh Station using HTML, PHP, CSS, JSON, AJAX and MySQL programming languages as database support. Broadly speaking, this research is divided into three stages, namely pre-development data collection, development and implementation, and post-development data collection. While in software development using the DSRM (Design Science Research Method) method. The news and event program information system is carried out by one of the administrative staff of the news and events program to record and input data on news and event program information. From the results of the study it can be concluded that the news and program information system at TVRI Aceh Station has followed the procedure using HTML, PHP, CSS, JSON, AJAX and MySQL programming languages as database support.